Correlation between compressive strength and ultrasonic pulse velocity of high strength concrete incorporating chopped basalt fibre - Shafiq, N. (American Institute of Physics Inc., 2015)
Ultrasonic pulse velocity (UPV), is considered as the most important test for non-destructive techniques that are used to evaluate the mechanical characteristics of high strength concrete (HSC). The relationship between the compressive strength of HSC containing chopped basalt fibre stands (CBSF) and UPV was investigated. The concrete specimens were prepared using a different ratio of CBSF as internal strengthening materials. The compressive strength measurements were conducted at the sample ages of 3, 7, 28, 56 and 90 days; whilst, the ultrasonic pulse velocity was measured at 28 days. The result of HSC's compressive strength with the chopped basalt fibre did not show any improvement; instead, it was decreased. The UPV of the chopped basalt fibre reinforced concrete has been found to be less than that of the control mix for each addition ratio of the basalt fibre. A relationship plot is gained between the cube compressive strength for HSC and UPV with various amounts of chopped basalt fibres. Â© 2015 AIP Publishing LLC.